Effect of topical fluoride application and diode laser-irradiation on white spot lesions of human enamel - Mohammad A. Alqahtani; Naif A. Almosa; Khalid A. Alsaif; Naif M. Alsaif; Yazeed J. Aljaser (Elsevier, 2021)
Objectives: This study aims to evaluate the effectiveness of topical fluoride application and diode laser-irradiation on the hardness of demineralized enamel and to evaluate the esthetic improvement of the white spot lesions (WSLs) using a visual analog scale (VAS). Materials and Methods: Artificial WSLs (3x3 mm) were created on the enamel surface of 45 human third molars. The teeth were randomly assigned into three groups (n = 15): group A, fluoride only; group B, combined therapy of fluoride and diode laser; and group C, control. Vicker's hardness number (VHN) was measured at baseline, after demineralization and after treatment. To evaluate the esthetic improvement after treatment, 14 raters evaluated each group's photographs using a 100-millimeter VAS. A one-way ANOVA or Brown-Forsythe and Games-Howell post hoc procedure were performed for statistical analysis. The level of significance was set at α = 0.05 for all tests. Results: Group A mean VHN was significantly higher than groups B and C, and group B was significantly higher than group C (P < 0.05). However, the mean VAS rating for the combined therapy group (B) was significantly higher than that for groups A and C (P < 0.05). Conclusion: Combination therapy significantly improved the esthetic appearance of WSLs compared to the fluoride only group. However, there was less enamel hardness versus treatment with fluoride only.